Strength of a Sandy Gypseous Soil Improved With Fly Ash Geopolymer - Qasim, Ahmed; Al-Sharrad, Muayad A. (Iraqi Journal of Civil Engineering, 2024)
This study investigates the strength performance and microstructural changes of a sandy gypseous soil improved with fly ash-based geopolymer, for shallow and deep applications. Different proportions of geopolymer were added to a natural gypseous soil having a gypsum content of 30% to 40% with different water contents. The fly ash was activated using sodium hydroxide with molar concentrations 8 and 12 molar and sodium silicate. The ratios of the fly ash to the activator were 1 and 2. Specimens were cured for different ages at 30°C. To simulate the field conditions, a number of specimens were immersed in a salt-saturated solution. Materials performance was evaluated at the macro level by performing unconfined compression test and at micro level by performing scanning electron microscopy test. The study showed that an increase in the molar concentration of sodium hydroxide and of the binder ratio improved material’s strength particularly at lower water contents of the soil. Increasing the binder content to about 30% improved the strength by enhancing the bonding between the soil particles. On the other hand, immersing the samples in the salt solution led, in most cases, to breakdown of the geopolymer network, as confirmed by the SEM images. It was concluded that the fly ash geopolymer-soil mixtures under investigation can provide as high as 8 MPa uniaxial strength under no sulfate attack. However, under sulfate attack condition, this strength can decrease to as low as 0.5 MPa. Even under the worst case, the later strength can be just enough to support shallow foundations rested on a saturated gypseous soil.